A potential disease monitoring and prognostic biomarker in cervical cancer patients: The clinical application of circular RNA_0018289. Issue 8 (22nd April 2020) - He, Jing; Lv, Xin; Zeng, Zhen
Abstract: Objective: This study aimed to investigate the tumor circular RNA_0018289 (circ_0018289) expression and its correlation with clinical characteristics as well as survival profiles in cervical cancer patients. Methods: A hundred and ninety‐two cervical cancer patients who received surgical resection were recruited in this prospective study. Tumor tissue and paired adjacent tissue were obtained during the surgery, in which circ_0018289 expression was detected by reverse transcription quantitative polymerase chain reaction. Disease‐free survival (DFS) and overall survival (OS) were recorded. Results: Circ_0018289 expression was upregulated in tumor tissue compared with paired adjacent tissue ( P < .001), and receiver operative characteristic curve disclosed its good value for separating tumor tissue from adjacent tissue with an area under curve of 0.907 (95% CI: 0.879‐0.935). Additionally, tumor circ_0018289 expression was positively associated with tumor size ( P = .009), lymph node metastasis ( P = .005) and Federation International of Gynecology and Obstetrics stage ( P = .005). The DFS ( P = .005) and OS ( P = .015) were both worse in patients with circ_0018289 high expression compared to patients with circ_0018289 low expression. Meanwhile, in patients with circ_0018289 high expression, DFS and OS were the longest in patients with high+ expression followed by patients with high++ expression, and the shortest in patients with high+++ expression. Moreover, circ_0018289 high expression could independently predict worse DFS in the total cervical cancer patients ( P = .042). Conclusion: Circ_0018289 could serve as a potential disease monitoring and prognostic biomarker in cervical cancer patients.